Pengaruh Insentif Terhadap Motivasi Kerja Karyawan PT Surabaya Multi Supplier - Arbaatun Cahyani Putri; Aisyah Darti Megasari; Nur Aini Anisa (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This article is intended to analyze the effect of incentives on the work motivation of PT. Surabaya Multi Supplier. Based on exposure to the results of questionnaire data processing using the SPSS Version 25.0 application in the hypothesis test using simple regression analysis, the calculated t value is 6,963> t table is 2,024, or the significance level is 0.000 < 0.05. Then the independent variable individually affects the dependent variable. While the magnitude of the correlation is 56.1%. This means that the hypothesis in this study is that Ha received incentive variables affect employee motivation variables at PT Surabaya Multi Supplier in Surabaya.